We can solve for x

f(x) = x^2 - 81

f(x) + 81 = x^2

√(f(x) + 81) = x

Your inverse function is

We have shown the positive branch of the square root. The inverse relation is actually double-valued, as x may be either sign and still give the same result for f(x).

f(x) = x^2 - 81

f(x) + 81 = x^2

√(f(x) + 81) = x

Your inverse function is

**f**^{-1}**(x) = √(x+81)**We have shown the positive branch of the square root. The inverse relation is actually double-valued, as x may be either sign and still give the same result for f(x).